Analisis Pengaruh Lingkungan Kerja, Budaya Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Kantor Kecamatan Palas Lampung Selatan - Wailmi, Khil; Trisnowati, Trisnowati (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The role of HR is increasingly evident in all competitions (Siswanto & Hamid, 2017), HR is the keyword in driving the organization, so that Human Resource Management becomes urgent in managing quality apparatus. This research topic brings together the existence of lower-level employees (sub-districts) with four research objects; work environment, work culture, leadership style and employee performance (ASN-THL). Do the work environment, work culture and leadership style have a significant effect simultaneously and partially on employee performance at the Palas District Office, South Lampung Regency? The type of research is an associative description based on the survey method, the research object is broken down into indicators as an instrument to explain the contribution of respondents. Partial correlation test Work environment (X1) with employee performance (Y), the closeness category is Very strong, Work Culture (X2) with employee performance (Y), the closeness category is quite Strong / moderate, Leadership Style (X3) with Employee Performance (Y), in the Low closeness category. Simultaneously Independent variables (X1,X2,X3), with dependent variables (Y) in the Very Strong correlation category. Hypothesis Significance (H1): accept Ha reject H0: significant effect. (H2): accept Ha rejected Ho: significant effect. H3: accept Ha rejected Ho: significant effect. Hypothesis Test F (simultaneous): variables X1, X2, X3 have a significant effect on variable Y (accept Ha rejected Ho) Regression analysis of X1 contribution to Y: positive effect, X2 to Y: positive effect, X3 to Y: negative effect and negative constant. Determination Coefficient; 74.5% is influenced by research variables and 26.5% is influenced by external factors.